Meta-analysis of the relationship between ocular and peripheral serum IL-17A and diabetic retinopathy - Li, Xiaodong; Qin, Wei; Qin, Xuewei; Wu, Dandan; Gao, Chenyuan; Luo, Yinyue; Xu, Mingchao (Frontiers in Endocrinology, 2024)
Purpose A systematic evaluation and Meta-analysis were performed to determine the relationship between IL-17A levels in ocular aqueous and peripheral venous serum samples and diabetic retinopathy (DR). Methods PubMed, Embase, Web of Science, and CNKI databases were searched from the time of library construction to 2023-09-20.The results were combined using a random-effects model, sensitivity analyses were performed to determine whether the arithmetic was stable and reliable, and subgroup analyses were used to look for possible sources of heterogeneity. Results A total of 7 case-control studies were included. The level of IL-17A was higher in the Nonproliferative DR(NPDR) group than in the Non-DR(NDR) group [SMD=2.07,95%CI(0.45,3.68),P=0.01], and the level of IL-17A in the proliferating DR(PDR) group was higher than that of the NDR group [SMD=4.66,95%CI(1.23,8.08),P<0.00001]. IL-17A levels in peripheral serum and atrial fluid were significantly higher in NPDR and PDR patients than in non-DR patients in subgroup analyses, and detection of peripheral serum IL-17A concentrations could help to assess the risk of progression from NPDR to PDR. Sensitivity analyses suggested that the results of the random-effects arithmetic were stable and reliable. Subgroup analyses based on assay method and sample source showed that the choice of these factors would largely influence the relationship between IL-17A levels and DR. Conclusion Elevated peripheral serum and ocular aqueous humor IL-17A levels in diabetic patients are associated with the risk of DR, IL-17A may serve as a potential predictor or therapeutic target for DR, and IL-17A may be an important predictor of inflammation for the progression of NPDR to PDR. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024532900.